The Protective Effect of Panax notoginseng Mixture on Hepatic Ischemia/Reperfusion Injury in Mice via Regulating NR3C2, SRC, and GAPDH - Hou, Wen; Wei, Bao; Liu, Hong Sheng (Frontiers in Pharmacology, 2021)
Panax Notoginseng mixture (PNM) has the characteristics of multi-component, multi-target and multi-effect, which can cope with the multi-directional and multi-dimensional complex pathological process caused by hepatic ischemia reperfusion injury (HIRI). Our animal experiments showed that PNM composed of Notoginseng, Dogwood and White peony root could significantly reduce the level of AST and ALT in the blood of mice with HIRI, indicating that this preparation had a protective effect on HIRI in mice. Therefore, the molecular mechanism of PNM intervention in HIRI was further explored by network pharmacology. Firstly, Target genes corresponding to active components and HIRI were obtained through databases such as TCMSP, Pharm Mapper, Swiss Target Prediction, GeneCards, etc. All Target genes were standardized by Uniprot database and a total of 291 Target genes with their intersection were obtained. Then, KEGG pathways and biological processes (BP) of 291 target genes were obtained through the online public platform of DAVID. A total of 177 KEGG pathways and 337 BP were obtained by setting P < 0.01 and FDR < 0.05. The network mapping map of components and disease targets was drew by Cytoscape, and the top 10 Hub target genes related to HIRI were obtained. At the same time, the STRING database was used to obtain the protein-protein interaction data set, which was imported into Cytoscape, and the first 10 Hub target genes were obtained. The Hub target genes obtained by the above two methods were molecular docking with their corresponding small molecule compounds through Dockthor online tool. The results showed that the docking of Paeoniflorin with GAPDH, Paeoniflorin and Loganin with SRC, ginsenoside Rb1 with NR3C2, Ursolic acid with IL6, etc. According to relevant literature reports, NR3C2, SRC and GAPDH were finally identified as target genes. After verification by immunohistochemical experiments, compared with the Sham group , the above three target genes were highly expressed in the HIRI group (P＜0.01). Compared with HIRI group, the expression of three target genes in PNM+HIRI group was significantly decreased (P＜0.01). The results showed that PNM could protect mouse HIRI by decreasing the expression of NR3C2, SRC, GAPDH.